The Effect of Social Media Marketing on Intention to Visit Through Local Wisdom - Widiantoro, Angger Bondan; Ardiansyah, Reza Eka; Ferdinand, Augusty Tae (LifeSciFi, 2024)
This study explores the interplay between Social Media Marketing (SMM) strategies and tourists’ intention to visit, mediated by local wisdom, within the framework of Community-Based Tourism (CBT) in Magelang, Indonesia. Employing a quantitative approach, this research gathers data from 100 respondents selected through purposive sampling, targeting active social media users interested in visiting Magelang. The findings reveal that SMM significantly enhances tourists' intention to visit both directly and indirectly via the perception of local wisdom. Local wisdom emerges as a pivotal mediator, fostering cultural authenticity and strengthening emotional bonds with the destination. This underscores its dual role as a cultural preservation tool and a strategic enhancer of destination appeal. The study provides novel insights into the integration of traditional cultural elements into contemporary digital marketing practices. By merging modern technological platforms with rich cultural narratives, this research advances the discourse on sustainable tourism marketing, particularly in underrepresented regions. Implications for policy makers, tourism marketers, and community stakeholders are discussed, highlighting the potential of CBT to foster economic growth, cultural sustainability, and community empowerment.